Perceptions on Multimedia technology by College of Education Teachers - Nachi Muthu; Vijaya Kumari (Intelektual Pustaka Media Utama, 2012)
Multimedia means, combination of text, audio, still images, animation, video and interactivity content forms delivered electronically. e-learning is a process and e-content is a product. The objectives of the study are to find out the significant relationship between the college of education teachers’ perception towards multimedia technology on the basis of gender wise, locality wise, maritial wise, subject wise, technical skill wise, experience wise and possessing degree wise. Evaluation of Multimedia Perception scale (EMPS) developed by the investigator with a relaibility of 0.89 and it collected 350 teachers from Tamil Nadu State of Indian Context. From the analysis, there is no significant differences between the perceptions of multimedia technology in terms of gender, locality and maritial status. The same perception was rejected on the basis of subject, technical skills, higher degree level and their experiences. The quality of learning depends not only on the form of how the process is carried out but also on what content is taught and how the content is presented.